2007
DOI: 10.1016/j.atherosclerosis.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical differences and atherosclerosis in apolipoprotein E-deficient mice with 129/SvEv and C57BL/6 genetic backgrounds

Abstract: There are well-known genetic background effects on atherosclerosis susceptibility in mice. To study the basis of these effects, we have generated the apolipoprotein E-null mutation in mouse embryonic stem cells of 129/SvEv origin, maintained it in the inbred strain (129-apoE), and compared these mice with those previously made in strain 129/Ola and backcrossed to a C57BL/6 genetic background (B6-apoE). Plasma cholesterol and triglyceride levels in the apoE-129 mice are twice the levels in apoE-B6, and both VLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 31 publications
3
60
1
Order By: Relevance
“…In the first study, Nachtigal et al showed that ApoE null mice on a standard chow develop attenuated atherosclerosis when crossbred with galectin-3 deficient mice [82]. A possible explanation for this difference is that, at variance with the study of Iacobini et al [81], while the wild-type mice were on a C57BL/6J background, the galectin-3 deficient mice were on a mixed background between C57BL/6J and 129/ SvEv, a strain which has long been recognized to be less prone to develop atherosclerotic lesions than the C57BL/6J [83,84]. In the second study, MacKinnon et al have also reported that galectin-3 ablation decreases atherosclerosis in ApoE-null mice fed a high-cholesterol Western diet [85].…”
Section: Galectin-3 As a Disease Mediator: Animal Studiescontrasting
confidence: 47%
“…In the first study, Nachtigal et al showed that ApoE null mice on a standard chow develop attenuated atherosclerosis when crossbred with galectin-3 deficient mice [82]. A possible explanation for this difference is that, at variance with the study of Iacobini et al [81], while the wild-type mice were on a C57BL/6J background, the galectin-3 deficient mice were on a mixed background between C57BL/6J and 129/ SvEv, a strain which has long been recognized to be less prone to develop atherosclerotic lesions than the C57BL/6J [83,84]. In the second study, MacKinnon et al have also reported that galectin-3 ablation decreases atherosclerosis in ApoE-null mice fed a high-cholesterol Western diet [85].…”
Section: Galectin-3 As a Disease Mediator: Animal Studiescontrasting
confidence: 47%
“…While the IL‐33 −/− mouse line was originally backcrossed for more than 10 generations into the C57BL/6 background, the backcross of the ST2 −/− mouse line is less complete with remnants of genetic material from the original 129 mouse strain 18. Of note, ApoE −/− mice in a 129 background have smaller lesions in the aortic roots 23 and the aorta 24 than ApoE −/− mice in a C57BL/6 background. Another possibility could be that ST2 has other ligands than IL‐33 or that IL‐33 has unique intracellular activities independent of ST2.…”
Section: Resultsmentioning
confidence: 99%
“…In these mice, intimal calcification is evident in atherosclerotic lesions of the aortic arch, the aorta, the pulmonary arteries, and the brachiocephalic arteries. 121,[123][124][125] LDLR-null mice fed a high-fat diet also develop intimal calcification in the proximal aorta, although this model is currently underutilized for the investigation of intimal calcification. 126,127 Cellular mediators of calcification Vascular calcification is an active cell-driven process which, in the context of atherosclerosis, may be orchestrated by differentiated intimal cells (SMCs or macrophages) or undifferentiated progenitor cells, either resident within the vessel wall or derived from the circulation.…”
Section: Atherosclerotic Calcificationmentioning
confidence: 99%